Dynamic efficiency: Intellectual capital in the chinese non-life insurance firms - Kweh Q.L.; Lu W.-M.; Wang W.-K. (Emerald Group Holdings Ltd., 2023)
Purpose – This paper aims to investigate the effect of intellectual capital (IC) on the operating efficiency of non-life insurance firms in China.Design/methodology/approach – The authors use a dynamic data envelopment analysis model called dynamic slacks-based measure (DSBM) model to estimate the operating efficiency of 32 Chinese non-life insurance firms. Using a panel data set for the period from 2006 to 2010, the authors run ordinary least squares (OLS) regressions to find the relationship between IC and efficiency performance.Findings – The authors find that the insurers have almost monotonically decreasing efficiency for the period from 2006 to 2010. Regression results show that human capital, structural capital and relational capital are significantly and positively related to operating efficiency.Research limitations/implications – This study suggests that managers of the Chinese non-life insurers should devote attention to the investments in IC to stay sustainable.Originality/value – This is the first paper to examine the impact of IC on operating efficiency in the Chinese non-life insurance industry. This study differs from prior studies in that the authors use the DSBM model proposed by Tone and Tsutsui (2010) for evaluating the operating efficiency using a dynamic process. © Emerald Group Publishing Limited 2014.